Work-related tension, using the methods of overcoming the stress and the affecting factors in emergency staff - Açik, Yasemin; Yiğitbaş, Çağla; Bulut, Aliye; Deveci, S. Erhan; Pirinçci, Edibe; Oğuzöncül, A. Ferdane; Rahman, Süheyla (Turkiye Klinikleri, 2016)
Objective: The purpose of the study is to determine work-related tension, using the methods of overcoming the stress and the affecting factors in emergency staff Material and Methods: The universe of the study in descriptive type is consisted of health team members in institutions rendering emergency health service belong to public sector in Turkey. Turkey was divided into 4 clusters (east, west, south and north) by taking the geographical settlement areas into consideration and a province was selected from each cluster in random. The number of people within the scope of the research is 769 and 560 people was reached (response rate is 72.82%). Approval of ethical committee and written permissions were acquired from the related institutions before the research. There are questions including the demographic characteristics of the participants and their opinions on the job in first section of the form in which data were gathered, and “Work-Related Tension Scale-WRTS” in the second section, and “Overcoming the Stress Scale-OSS” in the third section. The data were recorded in statistical program. The averages were given with standard deviations and p<0.05 was accepted as meaningful. Frequency analysis was carried out in the evaluation of the data and, Mann Whitney U test, Kruskall Wallis test and Spearman Correlation Analysis were implemented. Results: Average of age of the participants was 29.71±7.92 years. WRTS point average was 49.80±5.92 and was found high in young people, having low education level, in emergency medical technicians (EMT), the ones working on contract, having negative point of view against the occupation (p<0.05). OSS point average of the participants was 56.56±11.23. Conclusion: It was detected that WRTS point average in the participants was over scale point average and OSS point average was under scale point average. In health personnel rendering emergency service; service and training studies that will increase the level of using overcoming the stress methods, decrease the work-related tension and improve affecting factors should be given priority. © 2016 by Türkiye Klinikleri.
Acil sağlık çalışanlarında işe bağlı gerginlik, stresle başa çıkma yollarını kullanma durumu ve etkileyen faktörler
Keywords: Health personnel; Physiological; Stress